Frequency of raised Urinary Trypsinogen-2 in Acute Pancreatitis - Ali, Mansab; Syed Mehsam; Hussain, Adeel; Rasul, Shahid; Parveen, Sughra; Memon, Ahson; Aziz, Peer Asad (International Journal of Endorsing Health Science Research, 2017)
Objectives: To determine the frequency of raised Urinary Trypsinogen-2 in diagnosed patients of acute pancreatitis. Methodology: Settings Patients in emergency refer to General Surgery ward-3 Jinnah Post Graduate and Medical Centre Karachi. Duration Six months, started from 20-01-2012 to 19-07-2012. Study Design Cross sectional descriptive study. Subjects and Methods All cases of Acute Pancreatitis diagnosed by Upper Abdominal Pain, Raised Serum Amylase and/or Serum Lipase and Abdominal CT Scan findings, were included in the study. Urinary Trypsinogen-2 dipstick test was done. All patient related data including age, gender, sex and raised Urinary Trypsinogen-2 or normal, was recorded. Data analysis was done on SPSS version 10. Frequency and percentage was calculated for gender and raised trypsinogen-2. Age and gender wise stratification was done to see the effect of these variables on outcome. Results: Mean age of the patients was 38.14 ±7.42 years. The minimum age was 24 years, while the maximum age was 63 years. Raised urinary trypsinogen-2 level was present in 55 (65.5%) patients. Stratification of age group shows, that 40 (66.7%) patients in age group ≤ 40 years had raised urinary trypsinogen-2. Stratification of gender showed significant association with raised urinary trypsinogen-2 level (p-value 0.010). Conclusion: The frequency of raised Urinary Trypsinogen-2 in diagnosed patients of acute pancreatitis was found to be high.